Acute abdomen and septic shock in young lady treated conservatively. (August 2017) - Vasileios, Kaldis; Christos, Lampropoulos E.; Theodoros, Zarokostas; Tamta, Sirmpilantze; Natasa, Charalambous; Christina, Kordali; Tegonikou, Efi
Abstract : Introduction: Septic shock is a life-threatening condition that is accompanied by high mortality rates. It is defined as sepsis- induced hypotension that persists despite adequate fluid resuscitation and is associated with hypoperfusion abnormalities and organ dysfunction. Blood cultures are positive in only 40% to 60% of patients with clinical manifestations of septic shock. Aggressive treatment with broad-spectrum regimens and vasopressors is mandatory to increase survival. Case description: A 37-year-old lady presented to the emergency unit with an intense, sudden onset periumbilical pain with fever (39oC) and rigor, the last five hours. On physical examination, she was haemodynamically stable with rebound tenderness at palpation of right iliac fossa and right lateral ventricle. Abnormal laboratory tests were leukocytosis (WBC=19.500/µL, neutrophils=96.5%), hypoalbuminemia (3.4gr/dL) and elevated LDH (579U/L). She underwent abdominal CT scan with edema and inflammation of terminal ileum loops, high turbidity of mesenteric fat and high amount of free fluid. She was surgically evaluated and admitted in internal medicine department with triple antibiotic therapy and hydration. Results and conclusions: Just after admission, she had recurrent episodes of loss of consciousness and hypotension, refractory in administering fluids. She was treated, according to guidelines, as septic shock with vasopressors (noradrenaline) and broad-spectrum antibiotics (imipenem). She was informed of necessitation for urgent surgical intervention in case of response failure, however, she was gradually improved with postponement of surgery. Despite laboratory deterioration (WBC=44.000/µL, hypoalbuminemia=2.9gr/dL), she remained afebrile after the 2nd day with gradual symptoms' resolution and feeding the 5th day. She was discharged, free of symptoms, 7 days later. Blood cultures were negative. Abdominal MRI, upper and lower endoscopy were normal. Take-home message: Early diagnosis and treatment of septic shock is mandatory for rapid and effective treatment of this potentially fatal situation. Aggressive administration of vasopressors and antibiotics are life-saving and may avoid complications or painful therapeutic interventions, such as surgery.